«Marshall Plan» for Donbass: prerequisites for investment development - Kolosov, A.; Kolosova, K.; Savchenko, O.; Kucherenko, S. (Економічний вісник Донбасу, 2018)
The preconditions for restoration and investment development of Donbass according to the international "Marshall Plan" in case of peaceful settlement of armed conflict are determined. Significant advantages of Donbass as an object of the Marshall Plan implementation are shown, in particular, depending on the stages of the peaceful settlement in the Donbass, as well as the directions of investment of the enterprises of the largest cities of Donbas. The proposed estimation of volumes of annual investments, receipt of additional products, possibilities of its immediate consumption is offered.